A method for producing porous silicon-titanium composite materials by hydrochloric acid acid hydrolysis of titanium concentrate acid leaching residue

Porous silicon-titanium composite materials are produced by hydrochloric acid detoxification of titanium concentrate leach slag, and applied in the preparation of hydrated titanium dioxide, which solves the problem of difficult use of solid waste in the production process of titanium dioxide by hydrochloric acid, and achieves the comprehensive recycling of titanium and silicon and the environmentally friendly and pollution-free effect.

CN116060423BActive Publication Date: 2025-04-25PANZHIHUA QUANRUI IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310060126.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-12
Filing Date
2023-01-16
Publication Date
2025-04-25
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

In the production process of titanium dioxide by hydrochloric acid, solid waste is difficult to comprehensively utilize, and environmental protection issues have not been completely solved.

Method used

Porous silicon-titanium composite materials are produced by hydrochloric acid detoxification of titanium concentrate acid leach slag, and applied them to each process of hydrated titanium dioxide preparation as a precision filter aid to achieve a comprehensive recovery of titanium and silicon.

Benefits of technology

It has achieved a 100% yield of TiO2 and SiO2 in titanium concentrate raw materials, avoided the generation of solid waste, was environmentally friendly and pollution-free, and established a green circulation industrial chain.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116060423B_ABST
    Figure CN116060423B_ABST
Patent Text Reader

Abstract

The invention discloses a method for producing a porous silicon-titanium composite material by acid hydrolysis of titanium concentrate acid leaching residue using a hydrochloric acid method, comprising the following steps: acid addition, heating, cooling and hot filtration. The prepared porous silicon-titanium composite material is used as a precision filter aid in each process of preparing hydrated titanium dioxide to filter and purify ionic titanium and recover solid titanium. The filter cake obtained after filtering and purifying ionic titanium and recovering solid titanium has a titanium dioxide content of 46.84wt% after washing, drying or roasting, so that the TiO2 yield in the titanium concentrate raw material is 100% and the SiO2 yield is 100%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the technical field of titanium dioxide and titanium dioxide production, and in particular to an acidolysis method in an industrialized production process of titanium dioxide using a hydrochloric acid method from titanium concentrate, and more specifically to a method for producing a porous silicon-titanium composite material by acidolysis of titanium concentrate acid leaching residue using a hydrochloric acid method. Background Art

[0002] Titanium dioxide is the best white pigment in the world. At present, the mature processes for industrial production of titanium dioxide in the world are sulfuric acid method and chlorination method. The advantages of sulfuric acid method titanium dioxide manufacturing are easy access to mineral resources and relatively mature process technology. The disadvantages are long process route, high consumption of sulfuric acid and water, large amount of by-product ferrous sulfate that is difficult to fully utilize, difficult treatment of waste acid and wastewater, large environmental pollution, and high comprehensive cost at this stage. The advantages of chlorination method titanium dioxide production are short process and high product quality. The disadvantages are controlled raw materials, high-temperature chlorination and high-temperature oxidation have high process manufacturing requirements for the equipment itself, complex equipment structure, large investment, and high safety production risks due to the use of chlorine as the main raw material. The amount of slag washing wastewater and waste acid is large and difficult to treat.

[0003] After decades of exploration, some research results have been achieved in the production process of titanium dioxide by hydrochloric acid, but it has not actually reached the requirements of industrialization. The production of titanium dioxide by hydrochloric acid is to use hydrochloric acid to hydrolyze titanium concentrate or titanium slag to produce titanium liquid. The subsequent process is divided into two routes: one is to obtain titanium dioxide by hydrochloric acid through iron powder reduction to remove trivalent iron, concentration, freezing crystallization to remove ferrous chloride, hydrolysis, filtration and washing, drying, roasting and post-treatment; the other is to extract and separate Ti 4+ and Fe 2+ , Fe 3+ , Ca 2+ Mg 2+ The refined titanium liquid is treated by hydrolysis (or spray thermal hydrolysis), filtration, washing, drying, roasting and post-treatment to obtain hydrochloric acid titanium dioxide. There are also some literature reports that the titanium element is effectively separated by extracting various metal elements. The two main preparation processes of hydrochloric acid titanium dioxide in the world: the US ANI method (the main patent is US6440383) and the Canadian CTL method (the main patent is CA2513309), aiming at the extraction of titanium elements. However, the production process of hydrochloric acid titanium dioxide is not yet mature, the green recycling industry chain has not been established, the recycling of hydrochloric acid is not thorough, the solid waste cannot be comprehensively utilized, and the environmental protection problem has not been completely solved. At present, only Fujian Kuncai Materials Technology Co., Ltd. has been reported to use the hydrochloric acid extraction process to produce pearlite pigments of titanium dioxide.

[0004] The present invention utilizes the acid hydrolysis slag produced by the normal pressure hydrochloric acid acid hydrolysis system of titanium concentrate to prepare the porous silicon-titanium composite material; the porous silicon-titanium composite material is used as a high-efficiency and precise filter aid in various fine filtration links of the hydrochloric acid method titanium dioxide recycling industry chain; the adsorbed material after the porous silicon-titanium composite material adsorbs colloidal hydrated titanium dioxide and the like is used as the raw material of other industrial products, thereby realizing the full utilization of silicon and titanium resources in the raw materials; and the comprehensive utilization of solid waste and environmental protection problems in the hydrochloric acid method titanium dioxide production process are solved. Summary of the invention

[0005] The present invention produces a porous silicon-titanium composite material by acidolysis of titanium concentrate acid leaching residue using a hydrochloric acid method, and uses the prepared porous silicon-titanium composite material as a precision filter aid in each step of preparing hydrated titanium dioxide, and the composite material obtained after fine filtration is used as a by-product, thereby fully recovering titanium and silicon in the titanium concentrate raw material in the hydrochloric acid method titanium dioxide production process, avoiding the generation of solid waste, and being environmentally friendly and pollution-free.

[0006] To solve the above problems, the present invention adopts the following technical scheme: a method for producing porous silicon-titanium composite materials by acid leaching residue of titanium concentrate by hydrochloric acid method, characterized in that it comprises the following steps: opening the valve of the tail gas absorption acid storage tank, adding 550-650L tail gas absorption acid with a mass concentration of 28-30% into the closed acidolysis kettle, turning on the stirrer, adjusting the frequency to control the stirring speed to 30-40r / min, adding 400-480Kg of acidolysis slurry filter cake into the atmospheric pressure leaching pot by a spiral feeder, stirring to fully break up the acidolysis slurry filter cake, and directly heating the mixture with saturated steam. The temperature is raised to above 93°C, and hydrogen chloride gas produced by hydrochloric acid analysis or chloride salt roasting system is introduced. The free hydrochloric acid concentration of the system is >200g / L. The reaction is stirred for more than 3 hours, and the system temperature is cooled to 58-62°C. The discharge valve is opened and the system is pumped into a frame filter press for hot filtration and washing. The leaching mother liquor is pumped to the hydrochloric acid regeneration system for spray roasting, and the dissolution pores of the soluble compounds in the acid leaching residue particles are used to form pores, and the impurities of titanium pyroxene, silicon dioxide and other silicates in the titanium concentrate are converted into porous silicon-titanium composite materials. The porous silicon-titanium composite materials are dried by a rotary flash drying system.

[0007] Preferably, the tail gas absorption acid (28-30%) produced by the reduction acidolysis, hydrolysis and roasting system is added to the acidolysis kettle according to a certain ratio of hydrolysis concentrate L to acidolysis slag Kg (volume mass ratio 4:3-5:3), and then the acidolysis slag produced by the normal pressure hydrochloric acid acidolysis system of titanium concentrate is added under stirring, and the ore is mixed at room temperature. The saturated steam is directly heated to 95°C, and the hydrogen chloride gas produced by the hydrochloric acid analysis or chloride salt roasting system is introduced. The dissolution heat of the hydrogen chloride gas is used to maintain the system temperature, the acidity of the leaching system is increased, and the reaction is stirred for 3 hours, and the acidolysis titanium compounds and minerals are further leached. The dissolution pores of the soluble compounds in the acid leaching slag particles are used to form pores, and the impurities in the titanium concentrate such as titanium pyroxene, silicon dioxide and other silicates are converted into a porous silicon-titanium composite material with wide application value. During the reaction, the free hydrochloric acid concentration in the acidolysis kettle is maintained at >200g / L. When the system temperature drops to 60°C, the material is directly hot filtered and washed after discharge. The leaching mother liquor is spray-roasted by a hydrochloric acid removal regeneration system, and the porous silicon-titanium composite material is dried by a rotary flash drying system.

[0008] The present application uses the acid hydrolysis slag produced by the atmospheric hydrochloric acid acid hydrolysis system of titanium concentrate as raw material, and the tail gas absorption acid produced by the reduction acid hydrolysis, hydrolysis and roasting system as leaching agent, and the hydrogen chloride gas produced by the hydrochloric acid analysis or chloride salt roasting system is introduced to increase the acidity of the leaching system, and the dissolution heat of the hydrogen chloride gas is used to maintain the reaction temperature of the system, and the acid-lyzable titanium compounds and soluble minerals are further leached, and the dissolution pores of the soluble compounds in the acid leaching slag particles are used to form pores, so as to convert impurities in the titanium concentrate such as titanium pyroxene, silicon dioxide and other silicates into a porous silicon-titanium composite material with wide application value.

[0009] Beneficial effects:

[0010] By using hydrochloric acid to hydrolyze the acid leaching residue of titanium concentrate to produce porous silicon-titanium composite materials, the porous silicon-titanium composite materials are used as precision filter aids in each process of preparing hydrated titanium dioxide, and the composite materials obtained after fine filtration are used as by-products, so as to achieve a 100% TiO2 yield and a 100% SiO2 yield in the titanium concentrate raw material.

[0011] The prepared porous silicon-titanium composite filter material has excellent performance. In the pilot line of the green production industry chain of titanium dioxide by hydrochloric acid method of the applicant of the present invention, the application of this filter aid can filter and purify the ion titanium produced by the entire hydrated titanium dioxide system and recover the solid titanium:

[0012] (1) Ion titanium filtration purification: The acid solution after fine filtration through porous silicon-titanium composite filter material is the crystalline titanium liquid. The temperature is relatively high (70-80°C), and most of the ferrous chloride particles that have not yet crystallized to form ferrous chloride tetrahydrate solid are adsorbed;

[0013] (2) Recovery of solid titanium: The turbid washing acid formed by washing hydrated titanium dioxide is finely filtered through a porous silicon-titanium composite filter to produce clean washing acid;

[0014] (3) Recovery of solid titanium: The washing filtrate is treated by fine filtration with porous silicon-titanium composite filter material to produce washing water;

[0015] (4) Recovery of solid titanium: First, the porous silicon-titanium composite material mixed slurry produced by atmospheric pressure leaching is finely filtered through this material to generate a clean leaching mother liquor;

[0016] (5) The porous silicon-titanium composite material has excellent pore structure, adsorption characteristics and filtration performance, and can be used as a high-efficiency and precise filter aid in other chemical, metallurgical and other industries.

[0017] The filter cake obtained after filtering and purifying the ionic titanium produced by the entire hydrated titanium dioxide system and recovering the solid titanium has a titanium dioxide content of 46.84wt% after washing and drying (or calcining). It can be used as: (1) titanium dioxide raw material for ceramics; (2) raw material for nucleating agent in the production of microcrystalline glass; (3) composite material for photocatalysis; (4) titanium dioxide raw material for other products. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 SEM photo of the microporous structure of porous silicon-titanium composite material

[0019] Figure 2 Process diagram for preparing porous silicon-titanium composite material by acid hydrolysis of acid hydrolysis residue DETAILED DESCRIPTION

[0020] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0021] Embodiments of the present invention include:

[0022] Example 1

[0023] The composition of the acid hydrolysis slurry filter cake is: solid content 50%, dry basis TiO2: 35%, dry basis TFe: 29%, SiO2: 15%.

[0024] Open the valve of the tail gas absorption acid storage tank, add 600L of tail gas absorption acid (concentration: 29%) into the closed acidolysis kettle, start the stirrer, and adjust the frequency to control the stirring speed to 30-40r / min.

[0025] Use a screw feeder to add 450 kg of acid hydrolysis slurry filter cake into the atmospheric pressure leaching pot and stir for 30 minutes to fully break up the acid hydrolysis slurry filter cake.

[0026] Directly heat to 95°C using saturated steam.

[0027] Introduce hydrogen chloride gas generated by hydrochloric acid analysis or chloride salt roasting system, use the heat of solution of hydrogen chloride gas to maintain the system temperature, increase the free hydrochloric acid concentration of the system to >200g / L, and stir the reaction for 3 hours.

[0028] Open the jacket cooling water inlet and outlet valves for cooling, wait until the system temperature drops to 60°C, open the discharge valve, and pump into the frame filter press for hot filtration and washing. The leached mother liquor is pumped to the hydrochloric acid regeneration system for spray roasting, and the porous silicon-titanium composite material is dried using a rotary flash drying system.

[0029] Example 2

[0030] The composition of the acid hydrolysis slurry filter cake is: solid content 50%, dry basis TiO2: 35%, dry basis TFe: 29%, SiO2: 15%.

[0031] Open the valve of the tail gas absorption acid storage tank, add 600L of tail gas absorption acid (concentration: 30%) into the closed acidolysis kettle, start the stirrer, and adjust the frequency to control the stirring speed to 30-40r / min.

[0032] Use a screw feeder to add 460 kg of acid hydrolysis slurry filter cake into the atmospheric pressure leaching pot and stir for 30 minutes to fully break up the acid hydrolysis slurry filter cake.

[0033] The hydrogen chloride and steam mixed gas produced by the spray roasting system was introduced to heat the system to 95°C, and the acid hydrolysis temperature of the system and the free hydrochloric acid concentration in the acid hydrolysis kettle were maintained at ≥ 200 g / L. The reaction was stirred for 3 hours.

[0034] Open the jacket cooling water inlet and outlet valves for cooling, wait until the system temperature drops to 60°C, open the discharge valve, and pump into the frame filter press for hot filtration and washing. The leached mother liquor is pumped to the hydrochloric acid regeneration system for spray roasting, and the porous silicon-titanium composite material is dried using a rotary flash drying system.

[0035] Comparative Example 1

[0036] The regenerated acids used in Example 1 and Example 2 were produced in different batches and had slightly different concentrations.

[0037] The sources of HCl gas used in Example 1 and Example 2 are different: the HCl in Example 1 comes from the HCl produced by the hydrochloric acid analysis system, and the heat of dissolution of HCl is used to maintain the reaction system and increase the effective acidity of the system. The HCl and steam in Example 2 come from the hydrogen chloride and steam mixed gas produced by the spray roasting regeneration acid production system, and the hydrogen chloride and steam mixed gas is used to heat the reaction system and increase the effective acidity of the system.

[0038] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent process changes made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for producing porous silicon-titanium composite materials by hydrochloric acid acid hydrolysis of titanium concentrate acid leaching residue, characterized in that: The method comprises the following steps: opening the valve of the tail gas absorption acid storage tank, adding 550-650L tail gas absorption acid with a mass fraction of 28-30% into a closed acid hydrolysis kettle, starting a stirrer, adjusting the frequency to control the stirring speed to be 30-40r / min, adding 400-480Kg of acid hydrolysis slurry filter cake into a normal pressure leaching pot by a spiral feeder, stirring to fully break up the acid hydrolysis slurry filter cake, directly heating to above 93°C by saturated steam, and introducing hydrogen chloride gas generated by hydrochloric acid analysis or chloride salt roasting system. , the free hydrochloric acid concentration in the atmospheric pressure leaching pot is greater than 200g / L, the reaction is stirred for more than 3 hours, and the temperature in the atmospheric pressure leaching pot is cooled to 58-62℃, the discharge valve is opened, and the mixture is pumped into the frame filter press for hot filtration and washing; the leaching mother liquor is pumped to the hydrochloric acid regeneration system for spray roasting, and the dissolution pores of the soluble compounds in the acid leaching residue particles are used to form pores, and the impurities of titanium pyroxene, silicon dioxide and other silicates in the titanium concentrate are converted into porous silicon-titanium composite materials, and the porous silicon-titanium composite materials are dried by a rotary flash drying system.

2. The method for producing porous silicon-titanium composite materials by acidolysis of titanium concentrate and acid leaching residues using hydrochloric acid according to claim 1, characterized in that: 600L of tail gas absorption acid with a mass fraction of 29-30% was added into the closed acid hydrolysis kettle.

3. According to the method for producing porous silicon-titanium composite materials by hydrochloric acid acid hydrolysis of titanium concentrate acid leaching residues as described in claim 2, saturated steam is directly heated to 95°C, and the temperature in the atmospheric pressure leaching pot is cooled to 60°C.

4. The method for producing porous silicon-titanium composite materials by acid-lyzing titanium concentrate acid leaching residues using hydrochloric acid as claimed in claim 1, wherein the acid-lyzed slurry filter cake is composed of: Solid content 50%, dry basis TiO2: 35%, dry basis TFe: 29%, SiO2: 15%.

5. A method for producing porous silicon-titanium composite materials by acid leaching residue of titanium concentrate using hydrochloric acid method as described in claim 3, wherein 450 kg to 460 kg of acid slurry filter cake is added into a normal pressure leaching pot by a screw feeder, and stirred for 30 minutes to fully break up the acid slurry filter cake.

6. The porous silicon-titanium composite material obtained by the method for producing porous silicon-titanium composite materials by acid leaching residue of titanium concentrate using hydrochloric acid as described in claim 3 is used as a precision filter aid to filter and purify ionic titanium and recover solid titanium in each process of preparing hydrated titanium dioxide. The filter cake obtained after filtering and purifying ionic titanium and recovering solid titanium has a titanium dioxide content of 46.84wt% after washing, drying or roasting, so as to achieve a TiO2 yield of 100% and a SiO2 yield of 100% in the titanium concentrate raw material.

Citation Information

Patent Citations

  • Processing aqueous titanium chloride solutions to ultrafine titanium dioxide

    US6440383B1

  • High titanium hydrochloric acid leaching slag, new application thereof and preparation method of titanium pigment

    CN101935063A

  • Method for preparing titanium pigment by using titanium residues obtained by directly reducing titanium-iron oxide

    CN102627321A